Право соціального забезпечення в умовах гармонізації і реформування законодавства: основні аспекти - Клименко, А. Л.; Klymenko, A. L.; ORCID: http://orcid.org/0000-0001-9587-5827 (Теорія і практика правознавства. – 2019. – Вип. 1 (15). – C. 9-10, 2019)
Констатовано, що сучасне соціальне законодавство України є безсистемним, суперечливим, алогічним і застарілим. Наголошено на необхідності перегляду переліку категорій осіб, які мають потребу в забезпеченні й обслуговуванні внаслідок скрутних життєвих обставин, унеможлививши при цьому зловживання як з боку влади, так і з боку громадян. При цьому визнано доречним вивчення досвіду європейських країн з вирішення зазначеної проблеми.

The system and legislation in the field of social security require changes, improvements and harmonization with European standards. Thus, the main tasks of Ukraine on the way of reforming the system of social protection and ensuring is the study of the experience of market reforms in developed countries, the obligatory consideration of current trends. In addition, it is necessary to overcome the inconsistency, inconsistency and inconsistency of legislation in this area. This is possible if: it is possible to achieve the extension of social security only to citizens who are employed, their family members and persons who are not able to work; to fully introduce a differentiated approach, that is, they will receive adequate protection of the basic rights of the able- bodied, in particular, the right to work and its corresponding condition, receiving for this a special peace remuneration, as well as social insurance in case of loss of work, upon reaching retirement age, temporary or permanent disability, and the disabled are guaranteed material support and social services at the expense of social insurance and payments from state and local budgets; there will be a review and distribution of economic responsibility for the observance of social guarantees between the state, enterprises and citizens; the level of social guarantees will be established based on social standards, the most important of which are the minimum subsistence level, minimum wages and pensions, as well as social assistance amounts approved by the state; forms of social security of the population correspond to the degree of economic development.

Констатировано, что современное социальное законодательство Украины является бессистемным, противоречивым, алогичным и устаревшим. Сделан вывод о необходимости пересмотра перечня категорий лиц, которые нуждаются в обеспечении и обслуживании ввиду сложных жизненных обстоятельств, исключив при этом возможность злоупотреблений как со стороны власти, так и со стороны граждан. При этом признано уместным изучение опыта европейских стран в решении данной проблемы.
Тhe right of social security in the conditions of harmonization and reforming legislation: main aspects
Право социального обеспечения в условиях гармонизации и реформирования законодательства: основные аспекты
Клименко, А. Л. Право соціального забезпечення в умовах гармонізації і реформування законодавства: основні аспекти [Електронний ресурс] / А. Л. Клименко // Теорія і практика правознавства. – 2019. – Вип. 1 (15). – C. 9-10. – Режим доступу : https://doi.org/10.21564/2225-6555.2019.15.169640.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; соціальне законодавство; соціальна сфера; соціальне забезпечення; реформування; социальное законодательство; социальная сфера; социальное обеспечение; реформирование; social legislation; social sphere; social security; reformation; Україна. Ukraine. Украина